Human–Wildlife Conflicts: Does Origin Matter? - Cassini, Marcelo Hernan (2022)
Conservation biologists have divided wildlife in two antagonist categories—native and introduced populations—because they defend the hypothesis that the latter acquires or expresses harmful qualities that a population that remains in its original environment does not possess. Invasion biology has emerged as a branch of conservation biology dedicated exclusively to conflicts between introduced wildlife and human interest, including the protection of biodiversity. For invasion biology, the damage caused by native species is different and must be managed differently. However, the consensus around this native–introduced dichotomy is not universal, and a debate has intensified in recent years. The objective of this work was to compare the impacts of native and introduced species of terrestrial vertebrates of the United States using the dataset provided by Wildlife Services (WS), which depend upon the Animal and Plant Health Inspection Service of the Department of Agriculture. Annually, they receive thousands of reports and complaints of human–wildlife conflicts. I analyzed the WS databases and found, against expectations, that native species produce significantly more damage than nonnative ones, especially regarding damage to agriculture, property and health and safety. In the category of impacts on biodiversity and natural ecosystems, the differences were minor. I discuss several potential explanations of these patterns in the results. I also discuss the ecological foundations of the native–introduced dichotomy hypothesis.